(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Rhinosinusitis is the inflammation of nasal and paranasal sinus mucosa and is associated with mucosal alteration ranging from inflammatory thickening to gross nasal polyp formation. Concha bullosa is the term used for an aerated middle turbinate or a cell found within the middle turbinate. These structures appear as a widened area of the middle turbinate, and they may obstruct the ostio meatal complex. In the absence of a history of sinusitis, the incidental finding of widened middle turbinate during endoscopy or concha bullosa on computed tomography (CT) does not mandate further investigation. Objectives:To determine the symptoms described at presentation, radiological findings, endoscopy and to compare endoscopy and computed tomography scan findings of the nose and paranasal sinuses in patients with chronic rhinosinusitis before endoscopic sinus surgery. Methods: Forty three patients with chronic rhinosinusitis were studied. Physical history, ear, nose and throat examinations plus endoscopic examinations of nose and paranasal sinuses were performed. Computed tomography scan of the sinuses and ostiomeatal complex were done for all patients. Results:The patients aged 17 to 53 years (32.44 ± 9.83 years), and male to female ratio was 1.15:1. Headache is the commonest symptom (69.76%). The duration of symptom was 1-5 years in 44.18% of patients. Septal deviation was the most common finding 46.51% by endoscopic examination. Mucosal thickening present in all patients (100%) by CT-scan. Between endoscopic and CT scan findings There is a significant statistical difference for enlarged ethmoid bulla but not for septal deviation, abnormal uncinate proces and hypertrophy of inferior turbinate. Conclusion:Endoscopy and CT-scan of the nose and paranasal sinuses are mandatory before endoscopic sinus surgery of nose and paranasal sinuses in patients with chronic rhinosinusitis. Keywords:Chronic sinusitis, endoscope, CT-scan